Effect of In-Shoe Foot Orthosis Contours on Heel Pain Due to Calcaneal Spurs - Dwi Basuki Wibowo; Achmad Widodo; Gunawan Dwi Haryadi; Wahyu Caesarendra; Rudiansyah Harahap (Applied Sciences, 2019)
The objective of this study is to investigate the effect of contouring the shoe insole on calcaneal pressure and heel pain in calcaneal spur patients. Calcaneal pressure was measured using three force sensors from 13 patients including three males and 10 females. These patients have plantar heel pain due to calcaneal spurs, and we examined five customized contour insole foot areas (0⁻100%). Sensors were attached at the central heel (CH), lateral heel (LH) and medial heel (MH) of the foot. The pain was measured using an algometer and evaluated by the pain minimum compressive pressure (PMCP). In this study, it was observed that the calcaneal pressure decreased with increasing insole foot area. In addition, increasing the insole foot area from 25% to 50% can reduce the calcaneal pressure approximately 17.4% at the LH and 30.9% at the MH, which are smaller than the PMCP, while at the MH, pressure reduced 6.9%, which is greater than the PMCP. Therefore, to reduce pain, one can use 50% insole foot area, even though at MH it is still 19.3% greater than the PMCP. Excellent pain relief was observed when using 100% insole foot area, as the pressures in those three areas are lower than the PMCPs, but it is not recommended because it requires large production costs.